Wood Quality of Plantation Grown Azadlrachta Excelsa (Jack) Jacobs from Malaysia - Sing Boupha, Lathsami Boupha (1998)
Azadirachta exceIsa is a fast growing tree, with tall and straight clear bole. Six planted A. excelsa trees of three growth rates (dominant, co-dominant and suppressed) under the same site conditions and the same age were sampled at three height levels and three radial positions to provide specimens to investigate among growth-rates and within tree variations of anatomical, physical and mechanical properties. Mean vessel, ray and fibre contents were 18.99%, 19.08% and 62.74% respectively. Mean fibre length was 1.12 mm, fibre diameter 24.17µm, fibre lumen diameter l1.55µm, and fibre wall thickness 6.31µm. Mean specific gravity (SG) was 0.59, green moisture content 96.30%, tangential shrinkage 5.64%, radial shrinkage 2.61 % and volumetric shrinkage of 9.3%. Mean shear parallel to the grain was 13.34 MPa, compression parallel to the grain 41.95 MPa, modulus of elasticity (MOE) 6862 MPa, modulus of rupture (MOR) 83.85 MPa and hardness 3.03 kN. The anatomical, physical and mechanical properties of A. excelsa evaluated in this study were comparable to many of the light hardwood species. Therefore, the tree is suitable for a wide range of utilisation. Between growth-rate variations of all properties analysed showed significant difference. In general, dominant trees have thicker fibre wall, higher specific gravity and strength properties than the co-dominant and suppressed trees. The considerable variations in specific gravity, in strength and in anatomical parameters among" trees, if genetically controlled, offers possibilities for selection of breeding stock from seed or cuttings with desirable wood quality. Within tree variations was more pronounced in radial than in vertical direction, suggesting that diameter growth is an important factor contributing to the variations than the height growth. Samples from the midpoint between the pith and the bark were found to have highest specific gravity and also more dimensionally stable in dimension compared to the outer and inner part.